Effects of crude protein and sodium intake on water turnover in cats fed extruded diets - Garcia, Caroline A. [UNESP]; Loureiro, Bruna A. [UNESP]; Peres, Francine M. [UNESP]; Goloni, Camila [UNESP]; Di Santo, Ludmilla G. [UNESP]; Mendonca, Fernanda S. [UNESP]; Carciofi, Aulus C. [UNESP] (Wiley-Blackwell, 2020)
The comprehension of strategies to increase urine production may be important, especially in kibble diets to prevent urolithiasis in cats. The effects of increasing amounts of crude protein (CP) and sodium on the water turnover of cats were evaluated using the water balance (WB) method and the deuterium dilution technique. The study followed a randomized block design, with three blocks of eight cats, two cats per food type in each block, and six cats per food. Four extruded diets with different amounts of CP and sodium were evaluated (on DM basis): 28% CP and 0.58% sodium; 39% CP and 0.64% sodium; 52% CP and 0.76% sodium; and 64% CP and 0.87% sodium. Cats were individually housed in cages for 8 days to measure WB, urea excretion, and faecal and urine characteristics. Deuterium oxide was used to evaluate water turnover, and during the period cats were housed in a collective cattery. The data were analysed by anFtest, and the means were compared by polynomial contrasts. The alpha level of significance was set at 0.05. The methods were compared by Pearson correlation, and Bland and Altman analysis. The increase in the CP content elevated linearly the renal excretion of urea (p < .001), and, together with the higher sodium intake, elevated the renal solute load, which resulted in a linear increase in urine production and water intake (p < .01). The urine density, metabolic water, and faecal and insensible water losses did not differ (p > .05). The water flux increased linearly when using the deuterium method (p < .001), but the obtained values were 20.85 +/- 11.11 ml/cat/day higher than those verified using the WB method (p = .001). Higher CP and sodium amounts in dry diets increased the urine production and water consumption of cats, and this can be explored as a possible option to increase urination.
Keywords: deuterium; starch; urine; urolith